Evaluating crop-soil-water dynamics in waterlogged areas using a coupled groundwater-agronomic model. (September 2021) - Deng, Chenda; Zhang, Yao; Bailey, Ryan T.
Abstract: Waterlogging on croplands has been a known problem for a long time, leading to adverse social, physical, economic and environmental issues. To better solve the problem, the complicated plant-soil-water dynamics system needs to be better understood. The challenge is to simulate the interactions between the components in the systems. There are models that simulate plant-soil-water system but either run the processes independently leading to inaccuracy or has high invasiveness of using integrated models. This paper presents a tightly coupled model, DayCent-MODFLOW, that links a 3D ground-water flow (MODFLOW) model and a 1D agroecosystem model (DayCent). DayCent is responsible for plant-soil-water dynamic in the root zone, whereas MODFLOW simulates head and groundwater flow in the saturated zone of the aquifer. DayCent passes deep percolation from the soil profile to the water table and, under conditions of waterlogging in which the water table is within the soil profile, DayCent soil hydrologic processes are constrained by the presence of the water table simulated by MODFLOW. The coupling is achieved by adopting a parallel inter-process communication technique MPI (Message Passing Interface). The model is applied to a waterlogged agricultural area (22 km 2 ) in northern Colorado, USA and tested against groundwater head and rates of evapotranspiration (ET). The model runs in parallel with multiple processes on the largest AWS Linux server. Groundwater heads match measured heads to a reasonable degree, and ET rates match reference ET and are highly correlated with crop type. Results show the strong hydrologic interaction between the two models. Greenhouse gas emissions from soil (N2 O and CH4 ) were also estimated by the model under the waterlogged conditions. Although the model can be used to simulate any plant-soil-aquifer system, no matter the depth of the water table, results from this study show that the model can be used to assess crop productivity, recharge, ET, and greenhouse gas emissions in areas of shallow groundwater. Highlights: A new hydro-agronomic model is introduced by integrating the MODFLOW groundwater flow model and the DayCent 1D agronomic model. The crop-soil-water dynamics are better simulated in the waterlogged areas using the coupled model. MPI is utilized as communication tool for the coupling models to decrease overall run time and minimize code invasiveness. The model can assess recharge, and gas emissions under deep and shallow water table conditions in agricultural areas.